2018
DOI: 10.1097/iop.0000000000001112
|View full text |Cite
|
Sign up to set email alerts
|

Herpes Zoster Ophthalmicus With Orbital Findings Preceding Skin Rash

Abstract: The authors describe 2 patients who presented with orbital findings and later developed vesicular lesions that were positive for varicella zoster virus and consistent with Herpes Zoster ophthalmicus. One case is the first to involve dacryoadenitis and orbital myositis preceding disseminated Herpes Zoster. In the other case, a patient developed zoster orbital syndrome leading to elevated intraocular pressure, loss of vision, and afferent pupillary defect. Canthotomy and cantholysis were required to restore visi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 8 publications
0
13
0
2
Order By: Relevance
“…8 They demonstrated that enlargement of the extraocular muscles on computed tomography scan and symptom onset of acute orbital myositis developed 3 days before skin lesions. To our knowledge, there have been 12 cases of HZO preceding a skin lesion, [1][2][3][4][5][6][7][8][9][10] and the accompanying reports showed that the interval of zoster skin development after ocular involvement was a mean of 5.8 days (range, 2 to 10 days).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8 They demonstrated that enlargement of the extraocular muscles on computed tomography scan and symptom onset of acute orbital myositis developed 3 days before skin lesions. To our knowledge, there have been 12 cases of HZO preceding a skin lesion, [1][2][3][4][5][6][7][8][9][10] and the accompanying reports showed that the interval of zoster skin development after ocular involvement was a mean of 5.8 days (range, 2 to 10 days).…”
Section: Discussionmentioning
confidence: 99%
“…However, previous reports and our case showed enlargement of the lacrimal gland with other symptoms of acute orbital inflammation preceding a skin lesion. 7,9,10 Acute dacryoadenitis may be obscured by other symptoms, or it can be overlooked because of lack of routine imaging studies in patients with HZO. The empiric treatment of acute orbital inflammation in HZO is systemic acyclovir and steroids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical findings in the chronic phase include persistent corneal epithelial defects and postherpetic neuralgia. 8,[11][12][13] In the current report, we studied the ocular involvement of acute HZO. The age of onset of HZO for our cohort was about 50 years.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have reported devastating forms of ocular manifestations, such as orbital myositis, ophthalmoplegia, optic neuritis, cranial nerve palsy, and orbital apex syndrome. [11][12] Nonetheless, we should take special care with HZO patients who have decreased visual acuities. This state could indicate that the patient has a chance of developing serious ocular complications.…”
Section: Discussionmentioning
confidence: 99%